2004
DOI: 10.1074/jbc.m313209200
|View full text |Cite
|
Sign up to set email alerts
|

Ser/Arg-rich Protein-mediated Communication between U1 and U2 Small Nuclear Ribonucleoprotein Particles

Abstract: Previous work demonstrated that U1 small nuclear ribonucleoprotein particle (snRNP), bound to a downstream 5 splice site, can positively influence utilization of an upstream 3 splice site via exon definition in both trans-and cis-splicing systems. Although exon definition results in the enhancement of splicing of an upstream intron, the nature of the factors involved has remained elusive. We assayed the interaction of U1 snRNP as well as the positive effect of a downstream 5 splice site on trans-splicing in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Recent studies have shown that the RS domain of SR proteins bound to the exon can also interact directly with the BPS (6). Finally, SR proteins not only function by binding to ESEs, but they also play a critical role in the basic splicing mechanism within the intron, either by facilitating interactions between proteins bound to the 5Ј and 3Ј splice sites within the intron (24)(25)(26) and͞or by contacting the 5Ј splice site in the mature spliceosome (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the RS domain of SR proteins bound to the exon can also interact directly with the BPS (6). Finally, SR proteins not only function by binding to ESEs, but they also play a critical role in the basic splicing mechanism within the intron, either by facilitating interactions between proteins bound to the 5Ј and 3Ј splice sites within the intron (24)(25)(26) and͞or by contacting the 5Ј splice site in the mature spliceosome (27).…”
Section: Discussionmentioning
confidence: 99%
“…During exon definition, splice sites are recognized across the exon through the binding of U1 snRNP to the 59 splice site and U2AF and U2 snRNP binding to the upstream 39 splice site (Hoffman and Grabowski 1992;Chiara and Reed 1995;Boukis et al 2004;Sharma et al 2008). Splicing enhancers and silencers modulate the stability of these complexes, presumably by promoting or interfering with RS domain contacts (Graveley et al 2001;Boukis et al 2004). Exon defined splice sites must then transition to pair across the intron to mediate the assembly of the catalytic spliceosome.…”
Section: Components Of the Exon Definition Complex Are Retained On Spmentioning
confidence: 99%
“…Associations between the U1 snRNP protein U1 70k and the 39 splice site-bound protein U2AF have also been reported. This interaction was proposed to be mediated by the SR protein SC35 in mammals but by a direct contact in yeast (Wu and Maniatis 1993;Abovich and Rosbash 1997;Reed 2000;Boukis et al 2004). In HeLa cell extracts, the SR-related proteins Srm160 and Srm300 have also been shown to bridge the U1 and U2 snRNPs (Eldridge et al 1999;Blencowe et al 2000).…”
mentioning
confidence: 99%